The role of personality in becoming aware of age-related changes - Rupprecht, Fiona; Dutt, Anne J.; Wahl, Hans-Werner (GeroPsych, 2019)
Awareness of age-related change (AARC) refers to an individual’s conscious knowledge about the gains and losses resulting from growing older. Personality traits reflect dispositional patterns of behavior, perception, and evaluation and should therefore influence the experience of AARC. The 4.5-year longitudinal study examines this association between personality traits and AARC in a sample of 423 individuals aged 40 to 98 years (M = 62.9 years) using latent change analyses. After controlling for sex, health, and education, a different pattern of associations emerged for cross-sectional vs. longitudinal relations. Cross-sectionally, neuroticism was positively related to AARC losses, whereas openness, conscientiousness, and neuroticism were positively related to AARC gains. Longitudinally, the impact of personality traits on change in AARC was rather limited with only higher conscientiousness acting as a predictor of decreases in AARC losses over time. Overall, the findings add to the existing literature on associations between personality traits and subjective aging. Specifically, the results indicate that personality traits are differentially related to awareness of age-related gains in comparison to awareness of age-related losses.
Gesehen am 03.07.2020